"One man's meat is another man's poison": An experimental study of voluntarily providing public projects that raise mixed feelings - Werner Güth; Anastasios Koukoumelis; M. Vittoria Levati (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
We compare, on the basis of a procedurally fair provision point mechanism, bids for a public project from which some gain and some lose with bids for a less efficient public project from which all gain. In the main treatment, participants independently decide which one, if any, of the public projects should be implemented. We also run control treatments where only one of the two projects can be implemented. We find that (a) mixed feelings per se do not affect bidding behavior, and (b) the provision frequency of the project that raises mixed feelings declines significantly when it faces competition from the public good.
Keywords: C72; C92; D63; H44; 330; public project; bidding behavior; procedural fairness; Öffentliches Gut; Auktionstheorie; Gerechtigkeit; Emotion; Test